Evolution And Its Misinterpretation By The Scientific Community - Muhammad Owais Isaac (MAQOLAT: Journal of Islamic Studies, 2024)
Allah has created the heavens and the earth in stages as he declares in the Holy Quran.  It is Allah Who creates, develops and sustains life, and ensures harmony and diversity in all things, living and non-living. The verses from the Quran make it obvious that the conditions required for God’s ultimate creation to exist and survive are only possible if the universe contains matter, energy, water, and other entities as they are. The total measure of these entities cannot be altered, which means the total energy and matter in the universe is constant. These values are actually the result of the fine-tuned universe, where any deviation from it will lead to its instability and hence its extinction. This balance is maintained by the eternal and extremely intelligent being through His commands, and these commands, by observers, are conceived as laws of nature or scientific laws. This universe is solely meant for the trial of the ultimate creation, hence puzzling, brain-teasing, and other sorts of entangled phenomena in the observable universe are inevitable. This kind of nature is intentionally imparted to the universe by God to test mankind (God’s ultimate creation). The definition of biological evolution in modern science is actually an illusion and hence a trial for humans, since God calls this universe by the word "Garoor," meaning illusion or unreal. In conclusion, the misinterpretation of evolution by the scientific community can be attributed to the lack of understanding of the true nature of human existence and the purpose of life on Earth. By examining religious scriptures, we can see that humans are sent on Earth for minor and major trials by God, with minor trials such as evolutionary theory and other incomplete sciences being part of this category. It is evident that God initially formed the shape of a human from stagnant dark mud and then preserved it in a dry state. He did not breathe life into the mould until all the necessary conditions for human existence on Earth were ensured. After God infused life or spirit into the mould of Adam (AW), He taught Adam (AW) the names of things. Thus, it can be inferred that life on Earth was created by God in stages, and these stages are designed in a way that life and the species on Earth may appear to disbelievers as a result of natural selection or random evolution. However, as Muslims, it is important to remember that everything we observe in the universe is intended to test us by God, so it is best to avoid engaging in vague discussions on this matter. Know well that the life of this world is but an amusement and diversion, and adornment and boasting to one another, and competition in increase of wealth and children. This worldly life is no more than play and amusement. But the Hereafter is indeed the real life, if only they knew.(The Quran 29:64)